Does Glycyrrhizin Protect Against Ischemia- Reperfusion Induced Hepatic Injury By Inhibiting High-Mobility Group-1 (HMGB1) - A. Mabuchi; G. Gaidamaka; H. Watanabe; K. Wake; A. Wheatley; Marlini Muhamad (Elsevier, 2024)
Introduction: HMGB1 has been implicated in hepatic ischemiareperfusion (I/R) induced injury. Recently, glycyrrhizin (GL) has been shown to inhibit HMGB1 cytokine activity. In the current study, we tested the hypotheses (i) that GL protects the liver against I/R injury and (ii) the hepatoprotective effects of glycyrrhizin (GL) may in part be due to inhibition of HMGB1.